Federal state shareholdings in Russian companies: Origin, forms and consequences for enterprise performance - Alexander Muravyev (Bank of Finland, Institute for Economies in Transition (BOFIT), 2002)
This paper studies the impact of federal state shareholdings on the performance of Russian companies.It differs from most similar studies in two respects.Firstly, it focuses on mixed ownership companies rather than conventional state enterprises.Secondly, it distinguishes between several types of federal state shareholdings, namely elected blocks, residual blocks (which may be held by two bodies with different functions - the Ministry for State Property and the Russian Fund for Federal Property) and golden shares.The paper describes the origin of federal state shareholdings and discusses their possible implications for company performance. Econometric analysis shows that companies with state ownership generally perform worse than the average firm in terms of labour productivity and profitability.However, there are remarkable differences in the performance of companies with different types of state shareholdings.Companies with residual blocks held by the Property Fund are the worst performers, followed by companies with residual blocks held by the Ministry for State Property.Companies with elected shareholdings as well as with golden shares do not differ from the average enterprises in the respective industries. These differences in performance are explained by the different degrees of control the federal state has over enterprises with various types of shareholdings - greater control is associated with better performance.The paper concludes that the government should avoid keeping equity stakes in companies unless there is a good reason to retain them.If the state wants to keep an ownership stake in a company, reliable control structures must be created. Finally, the issue of golden shares in strategically important companies seems to be a reasonable alternative to retaining some control over them through equity ownership.
URN:NBN:fi:bof-201408072042
Keywords: 330; Corporate governance; state ownership; firm performance; Russia